Core–Shell Structured C@SiO2 Hollow Spheres Decorated with Nickel Nanoparticles as Anode Materials for Lithium‐Ion Batteries. Issue 49 (27th October 2021) - Liu, Tao; Qu, Yinhu; Liu, Jiahao; Zhang, Liuyang; Cheng, Bei; Yu, Jiaguo
Abstract: Silicon oxide is regarded as a promising anode material for lithium‐ion batteries owing to high theoretical capacity, abundant reserve, and environmental friendliness. Large volumetric variations during the discharging/charging and intrinsically poor electrical conductivity, however, severely hinder its application. Herein, a core–shell structured composite is constructed by hollow carbon spheres and SiO2 nanosheets decorated with nickel nanoparticles (Ni‐SiO2 /C HS). Hollow carbon spheres, as mesoporous cores, not only significantly facilitate the electron transfer but also prominently enhance the mechanical robustness of anode materials, which separately improves the rate performance and the cyclic durability. Besides, ultrathin SiO2 nanosheets, as hierarchical shells, provide abundant electrochemical active surface for capacity increment. Moreover, nickel nanoparticles boost the transport capacity of electrons in SiO2 nanosheets. Such a unique architecture of Ni‐SiO2 /C HS guarantees an enhanced discharge capacity (712 mAh g −1 at 0.1 A g −1 ) and prolonged cyclic durability (352 mAh g −1 at 1.0 A g −1 after 500 cycles). The present work offers a possibility for silica‐based anode materials in the application of next‐generation lithium‐ion batteries. Abstract : The core–shell structured silica‐based hollow spheres (Ni‐SiO2 /C HS) are successfully synthesized via a template‐engaged method along with thermal reduction. In the architecture, carbon hollow spheres and SiO2 nanosheets decorated with nickel nanoparticles serve as mesoporous cores and hierarchical shells, respectively. Such a unique architecture of Ni‐SiO2 /C HS guarantees an enhanced discharge capacity and prolonged cyclic durability.